Hypertension and diabetes control along the HIV care cascade in rural South Africa. Issue 3 (27th March 2019) - Manne‐Goehler, Jennifer; Siedner, Mark J; Montana, Livia; Harling, Guy; Geldsetzer, Pascal; Rohr, Julia; Gómez‐Olivé, F Xavier; Goehler, Alexander; Wade, Alisha; Gaziano, Thomas; Kahn, Kathleen; Davies, Justine I; et al.
Abstract: Introduction: Participation in antiretroviral therapy (ART) programmes has been associated with greater utilization of care for hypertension and diabetes in rural South Africa. The objective of this study was to assess whether people living with HIV on ART with comorbid hypertension or diabetes also have improved chronic disease management indicators. Methods: The Health and Aging in Africa: a longitudinal study of an INDEPTH Community in South Africa (HAALSI) is a cohort of 5059 adults >40 years old. Enrollment took place between November 2014 and November 2015. The study collected population‐based data on demographics, healthcare utilization, height, weight, blood pressure (BP) and blood glucose as well as HIV infection, HIV‐1 RNA viral load (VL) and ART exposure. We used regression models to determine whether HIV care cascade stage (HIV‐negative, HIV+ /No ART, ART/Detected HIV VL, and ART/Undetectable VL) was associated with diagnosis or treatment of hypertension or diabetes, and systolic blood pressure and glucose among those with diagnosed hypertension or diabetes. ART use was measured from drug level testing on dried blood spots. Results and discussion: Compared to people without HIV, ART/Undetectable VL was associated with greater awareness of hypertension diagnosis (adjusted risk ratio (aRR) 1.18, 95% CI: 1.09 to 1.28) and treatment of hypertension (aRR 1.24, 95% CI: 1.10 to 1.41) among those who met hypertension diagnostic criteria. HIV care cascade stage was not significantly associated with awareness of diagnosis or treatment of diabetes. Among those with diagnosed hypertension or diabetes, ART/Undetectable VL was associated with lower mean systolic blood pressure (5.98 mm Hg, 95% CI: 9.65 to 2.32) and lower mean glucose (3.77 mmol/L, 95% CI: 6.85 to 0.69), compared to being HIV‐negative. Conclusions: Participants on ART with an undetectable VL had lower systolic blood pressure and blood glucose than the HIV‐negative participants. HIV treatment programmes may provide a platform for health systems strengthening for cardiometabolic disease.